Risk Factors Associated with the Colonization of Multidrug-Resistant Gram-Negative Bacteria Upon Admission to the Intensive Care Unit: A Cross-sectional Study - Nina Sania; Yulia Rosa Saharman; Delly Chipta Lestari; Dita Aditianingsih; Andi Yasmon (Acta Medica Indonesiana)
Background: Multidrug-resistant Gram-negative bacteria (MDR-GNB) are prevalent in intensive care units (ICUs), leading to increased morbidity and mortality. Limited data on MDR-GNB in Indonesia prompted this study to determine the prevalence and risk factors associated with MDR-GNB colonization, enhancing screening strategies, and acquiring phenotypic and genotypic data on these bacteria. Methods: This analytical cross-sectional observational study included participants who met the criteria and were admitted to the ICU at Dr. Cipto Mangunkusumo Hospital from January to December 2022. We used multivariate analysis on the findings from rectal swab screening, sociodemographic, clinical, and microbiological examinations. Results: Out of 108 participants, 172 cultures comprised 165 Gram-negative isolates, four yeasts, and three with no growth. The prevalence of patients colonized with MDR-GNB was 51.85% (56/108), and the prevalence of MDR-GNB isolates was 39.53% (68/172), with the most common MDR-GNB being Escherichia coli (29.65%) and Klebsiella pneumoniae (19.44%). The most resistant gene found in ESBL was CTX-M (75%), and the carbapenemase producer gene was NDM (5.88%). Risk factors associated with MDR-GNB colonization were the length of stay before admission to the ICU (p = 0.003) and a history of previous antibiotic therapy (p = 0.036). Conclusion: In this study, two risk factors were associated with the occurrence of MDR-GNB colonization, with the prevalence of MDR-GNB colonization in patients initially admitted to the ICU still quite high. Therefore, selecting screening patients based on risk factors at the time of initial admission to the ICU is crucial for infection control programs.